Glyoxalase I‐4 functions downstream of NAC72 to modulate downy mildew resistance in grapevine. (21st August 2021) - Li, Tiemei; Cheng, Xin; Wang, Xiaowei; Li, Guanggui; Wang, Bianbian; Wang, Wenyuan; Zhang, Na; Han, Yulei; Jiao, Bolei; Wang, Yuejin; Liu, Guotian; Xu, Tengfei; et al.
Summary: Glyoxalase I (GLYI) is part of the glyoxalase system; its major function is the detoxification of α‐ketoaldehydes, including the potent and cytotoxic methylglyoxal (MG). Methylglyoxal disrupts mitochondrial respiration and increases production of reactive oxygen species (ROS), which also increase during pathogen infection of plant tissues; however, there have been few studies relating the glyoxalase system to the plant pathogen response. We used the promoter of VvGLYI‐4 to screen the upstream transcription factors and report a NAC (NAM/ATAF/CUC) domain‐containing transcription factor VvNAC72 in grapevine, which is localized to the nucleus. Our results show that VvNAC72 expression is induced by downy mildew, Plasmopara viticola, while the transcript level of VvGLYI‐4 decreases. Further analysis revealed that VvNAC72 can bind directly to the promoter region of VvGLYI‐4 via the CACGTG element, leading to inhibition of VvGLYI‐4 transcription. Stable overexpression of VvNAC72 in grapevine and tobacco showed a decreased expression level of VvGLYI‐4 and increased content of MG and ROS, as well as stronger resistance to pathogen stress. Taken together, these results demonstrate that grapevine VvNAC72 negatively modulates detoxification of MG through repression of VvGLYI‐4, and finally enhances resistance to downy mildew, at least in part, via the modulation of MG‐associated ROS homeostasis through a salicylic acid‐mediated defense pathway. Significance Statement: We show that VvNAC72 responds to the grapevine ( Vitis vinifera ) pathogen powdery mildew Plasmopara viticola and binds to the promoter region of VvGLYI‐4 at a specific binding site. This can explain the downregulation of VvGLYI‐4 during powdery mildew stress, following increasing amounts of VvGLYI‐4 enzyme degradation products methylglyoxal and reactive oxygen species, leading to strong resistance to P. viticola . This discovery highlights the role of VvNAC72 and VvGLYI‐4 in stress responses and pathogen defense in grapevine.